KAJIAN PENERAPAN SOIL NAILING EKONOMIS SEBAGAI PENGUAT SLOPE STABILITY PADA KAWASAN WISATA LEMBANG BANDUNG - Nurcaweda Riztria Adinda (ENSAINS JOURNAL, 2019)
Abstract: The increasing interest of urban communities to tour the slopes has resulted in the development of tourist areas, especially in the area of increased slopes. Like the tourist area of Lembang Bandung which has a tourist concept in the slope area. However, it is not only the beauty factor that is prioritized, but also the safe factors of the slope stability in the slope area are considered by the community. One form of anticipation towards the safe factor slope stability that can be applied is one of them is the application of soil nailing. The soil nailing method is currently highly developed, there are various methods of work on Soil Nailing. The work method of soil nailing applied to the Lembang Bandung tourist area project is a soil nailing method that uses bamboo material as nails and wire as a soil coating, then finishing by a cement mixture with the application of rough stucco technique. The nails material that is generally used is concrete iron, but this time bamboo material was chosen as a nails because the availability of bamboo material around the Lembang area of Bandung is quite large so the price is quite cheap. By replacing the Ø 10 mm concrete iron material into bamboo Ø 7-10 cm as nails, then the cost that can be cut reaches Rp. 73,014 / m² or the efficiency achieved is ± 35,7%, of course, by not overriding the function and strength of the soil nailing.Keywords : soil nailing, bamboo, soilAbstrak: Meningkatnya minat masyarakat urban untuk berwisata di kawasan lereng mengakibatkan pembangunan kawasan wisata terutama di kawasan lereng meningkat. Seperti halnya kawasan wisata Lembang Bandung yang memiliki konsep wisata di kawasan lereng. Namun, tidak hanya faktor keindahan saja yang diutamakan tetapi juga safe factor dari slope stability di kawasan lereng tersebut menjadi pertimbangan masyarakat. Bentuk antisipasi terhadap safe factor slope stability yang dapat diterapkan adalah salah satunya dengan penerapan soil nailing. Metode soil nailing saat ini sangat berkembang, terdapat berbagai macam metoda kerja pada Soil Nailing. Metode kerja soil nailing yang diterapkan pada proyek kawasan wisata Lembang Bandung ini adalah metode soil nailing yang menggunakan material bambu sebagai nails dan ram kawat sebagai pelapis tanah, kemudian finishing oleh campuran semen dengan aplikasi teknik kamprot kasar. Material nails yang pada umumnya digunakan adalah besi beton, namun kali ini dipilihnya material bambu sebagai nails karena ketersediaan material bambu di sekitar kawasan Lembang Bandung yang cukup banyak sehingga harganya cukup murah. Dengan mengganti material besi beton Ø 10 mm menjadi bambu Ø 7-10 cm sebagai nails, maka biaya yang dapat dipangkas mencapai Rp. 73.014/m² atau efisiensi yang tercapai sebesar ± 35,7 % tentunya dengan tidak mengesampingkan fungsi dan kekuatan dari soil nailing tersebut.Kata kunci : soil nailing, bambu, tanah